2023
DOI: 10.1002/hsr2.1203
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to receive COVID‐19 booster dose and its associated factors in Ghana: A cross‐sectional study

Abstract: Background and Aim The COVID‐19 booster dose has been cited as an important supplement for the control of the COVID‐19 pandemic due to reports of waning immunity among fully vaccinated persons. Determining factors that would affect its acceptability is necessary for initiating successful vaccination programs. In this study, we aimed to evaluate the factors associated with the acceptability of the COVID‐19 booster dose in Ghana. Methods We conducted an online cross‐secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Furthermore, our results are comparable to those reported in Chile (88.2%). However, this result contrasts significantly with the situation in Ghana, where only 46.2% of adults have a high intention to be vaccinated (IBV) ( Storph et al, 2023 ). However, a systematic review indicated that the IBV of the booster dose is different from the actual vaccine uptake ( Abdelmoneim et al, 2022 ) .…”
Section: Discussioncontrasting
confidence: 68%
“…Furthermore, our results are comparable to those reported in Chile (88.2%). However, this result contrasts significantly with the situation in Ghana, where only 46.2% of adults have a high intention to be vaccinated (IBV) ( Storph et al, 2023 ). However, a systematic review indicated that the IBV of the booster dose is different from the actual vaccine uptake ( Abdelmoneim et al, 2022 ) .…”
Section: Discussioncontrasting
confidence: 68%
“…According to Freeman et al [39](2022), there is evidence suggesting that hesitancy is more prevalent among those who identify as female, have lower income levels, and belong to certain ethnic groups. Adverse side effects of the vaccines [9], [13], [15], [26], [28], [30], [32], [42] 8 2 Mistrust in the vaccine [8], [32], [37], [42],[43] 5 3…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…Not confident in the safety of the vaccines [7], [26], [30], [44] The significance of demographic analysis is in the provision of valuable information that can inform effective decision-making processes undertaken by governmental bodies and social service organizations [40,41]. Additionally, it aids individuals in comprehending the attributes of a certain population and its potential future transformations, a crucial aspect in informing decision-making processes.…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If it subsequently proves to be true, vaccination campaigns against both infections can be combined to reduce the total intervention cost; thus, a combination vaccine can be crucial. Moreover, the willingness to receive COVID-19 booster doses is significantly lower than that for primary vaccinations 7 10 . Combining influenza vaccines with COVID-19 booster doses might increase uptake of the latter since many populations are accustomed to receiving annual influenza vaccines 11 , 12 .…”
Section: Introductionmentioning
confidence: 97%